Methylation-specific multiplex ligation-dependent probe amplification (MS-MLPA) robustly detects and distinguishes 11p15 abnormalities associated with overgrowth and growth retardation. Issue 2 (15th October 2007) - Scott, R H; Douglas, J; Baskcomb, L; Nygren, A O; Birch, J M; Cole, T R; Cormier-Daire, V; Eastwood, D M; Garcia-Minaur, S; Lupunzina, P; Tatton-Brown, K; Bliek, J; et al.
Abstract : Background: A variety of abnormalities have been demonstrated at chromosome 11p15 in individuals with overgrowth and growth retardation. The identification of these abnormalities is clinically important but often technically difficult. Methylation-specific multiplex ligation-dependent probe amplification (MS-MLPA) is a simple but effective technique able to identify and differentiate methylation and copy number abnormalities, and thus is potentially well suited to the analysis of 11p15. Aims: To customise and test an MS-MLPA assay capable of detecting and distinguishing the full spectrum of known 11p15 epigenetic and copy number abnormalities associated with overgrowth and growth retardation and to assess its effectiveness as a first line investigation of these abnormalities. Methods: Five synthetic probe pairs were designed to extend the range of abnormalities detectable with a commercially available MS-MLPA assay. To define the normal values, 75 normal control samples were analysed using the customised assay. The assay was then used to analyse a "test set" of 24 normal and 27 abnormal samples, with data analysed by two independent blinded observers. The status of all abnormal samples was confirmed by a second technique. Results: The MS-MLPA assay gave reproducible, accurate methylation and copy number results in the 126 samples assayed. The blinded observers correctly identified and classified all 51 samples in the test set. Conclusions: MS-MLPA robustly and sensitively detects and distinguishes epigenetic and copy number abnormalities at 11p15 and is an effective first line investigation of 11p15 in individuals with overgrowth or growth retardation.